How to identify promising chances for technological innovation: Keygraph-based patent analysis. (October 2020) - Geum, Youngjung; Kim, Mirae
Abstract: Few would argue that technology has driven numerous innovations. Therefore, the body of literature has been almost unanimous in employing patent information to identify opportunities. Previous studies using patent database employed a frequency-based approach, which assumes that frequent keywords play a key role in innovation. However, innovations can occur not only from frequent trends, but also from infrequent trends. Some previous research, albeit infrequent, has attempted keygraph approach in order to reflect infrequent trends to the new innovation development. Despite the effort, however, little is known about effective interpretation of keygraph results to identify new opportunities. Therefore, we suggested a keygraph-based approach combined with the index-based validation approach. We conducted a case study on healthcare services to illustrate the effectiveness of the proposed approach.